Cinobufagin alleviates lipopolysaccharide-induced acute lung injury by regulating autophagy through activation of the p53/mTOR pathway - Wang, Cheng; Mei, Xianghuang; Wu, Yanrong; Yang, Yuting; Zeng, Zhenguo (Frontiers in Pharmacology, 2022)
Acute lung injury (ALI) is a severe clinical disorder characterized by dysregulated inflammatory responses, leading to high rates of morbidity and mortality. Cinobufagin, a primary component isolated from cinobufotalin, exerts strong anticancer effects. However, there are few reports on its role in ALI, and it is unclear whether cinobufagin affects lipopolysaccharide (LPS)-induced ALI. Therefore, the present study aimed to investigate the effect of cinobufagin on LPS-induced ALI and to assess its potential mechanism of action. The results showed that cinobufagin alleviated lung histopathological changes and protected the permeability of lung tissues in LPS-induced ALI. In addition, cinobufagin effectively suppressed inﬂammatory responses through the induction of autophagy in LPS-induced ALI cells and in a mouse model. Moreover, cinobufagin enhanced autophagy through the p53/mTOR pathway in LPS-induced ALI. Herein, it was reported for the first time that cinobufagin inhibited the inﬂammatory response of LPS-induced ALI, which laid the foundation for further understanding and development of cinobufagin as a potential new drug for ALI.